The Role of Education in Shaping Women’s Autonomy: A Comparative Study of Rural and Urban Areas - Radha, P; Sayyed , Nazreen; V, Kushal Babu (International Journal of Atharva, 2025)
Education is a critical factor in shaping women's autonomy, impacting their ability to make informed decisions, access opportunities, and participate fully in societal and economic activities. This comparative study examines the role of education in enhancing women's autonomy in rural and urban areas, highlighting the disparities and unique challenges faced in different contexts. The research investigates how educational attainment influences women's self-efficacy, economic independence, and social status across diverse environments. It contrasts urban areas, characterized by greater access to educational resources, with rural areas, where educational opportunities are often limited and socio-cultural constraints can be more pronounced. Data was collected through surveys, interviews, and case studies involving women from both settings to assess their educational experiences and perceived autonomy.Key findings reveal that while education significantly empowers women in both rural and urban contexts, the extent and nature of this empowerment vary. In urban areas, women with higher educational levels experience greater economic and social autonomy, facilitated by better access to resources, employment opportunities, and supportive networks. Conversely, rural women often face educational barriers due to limited infrastructure, traditional gender roles, and economic constraints, which impede their autonomy despite educational advancements. The study underscores the need for targeted policies that address these disparities, emphasizing the importance of improving educational access and quality in rural areas while continuing to support and expand opportunities in urban settings. Recommendations include enhancing educational infrastructure, promoting gender-sensitive curricula, and fostering community-based initiatives to support women's education and autonomy in both environments. This research highlights the integral role of education in shaping women's autonomy and advocates for a nuanced approach to educational policy and practice that considers the diverse needs of women in varying geographic and socio-economic contexts.